2017
DOI: 10.18203/2349-2902.isj20170849
|View full text |Cite
|
Sign up to set email alerts
|

Study of laparoscopic appendectomy: advantages, disadvantages and reasons for conversion of laparoscopic to open appendectomy

Abstract: Background:Good outcome has been reported with the laparoscopic approach in uncomplicated appendicitis, but a higher incidence of postoperative intraabdominal abscesses has been reported after laparoscopic appendectomy in complicated appendicitis. Objective was to study the efficacy of laparoscopic appendectomy.Methods: A Hospital based cross sectional study was carried out among of 302 patients. The study duration was from June 2004 to December 2006. Institutional Ethics Committee permission was obtained. Inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 8 publications
0
3
1
Order By: Relevance
“…Similar to this, Yagnik found that the laparoscopic appendectomy had a considerably lower SSI rate than the open appendectomy (10.63% in OA vs 1.92% in LA)23 . Laparoscopic appendectomy had rate of wound infection that was much lower than open appendectomy in this study (10.9% in the OA group vs 1.8% in the LA group)24 . The outcomes are equivalent to those of earlier research.…”
contrasting
confidence: 52%
“…Similar to this, Yagnik found that the laparoscopic appendectomy had a considerably lower SSI rate than the open appendectomy (10.63% in OA vs 1.92% in LA)23 . Laparoscopic appendectomy had rate of wound infection that was much lower than open appendectomy in this study (10.9% in the OA group vs 1.8% in the LA group)24 . The outcomes are equivalent to those of earlier research.…”
contrasting
confidence: 52%
“…16,17 In 2017 a research concluded that LA is better than OA with respect to the wound infection, duration of hospital stay, earlier return to normal activity, better cosmetic appeal, and lesser use of antibiotics. 18 Most studies chose LA to be the golden standard for any appendectomy due to its safe and more effective surgical approach than OA. Except for Kocata et al who have stated that 'laparoscopic approach to appendectomy for patient with uncomplicated appendicitis doesn't offer a significant advantage over the open approach'.…”
Section: Discussionmentioning
confidence: 99%
“…The control group here is the OA group, it's considered as a 'fake' or 'sham surgical' control group in surgical RCTs as it wouldn't be ethical to blind surgeons and patients from surgical interventions. 18,19 Various systematic reviews conducted to evaluate the same topic, focused particularly on the duration of hospital stay. Most of them reached to the same conclusion that LA is the gold standard treatment (intervention) for appendicitis.…”
Section: Discussionmentioning
confidence: 99%
“…Laparoscopic appendectomy is also associated with decreased rates of wound contamination. The only downside to laparoscopic appendectomy may be that the earliest research on laparoscopic appendectomy suggested a higher rate of infection when this procedure was used for perforated appendicitis [9][10][11].…”
Section: Introductionmentioning
confidence: 99%